Post-treatment With Irisin Attenuates Acute Kidney Injury in Sepsis Mice Through Anti-Ferroptosis via the SIRT1/Nrf2 Pathway - Qiongyue, Zhang; Xin, Yang; Meng, Peng; Sulin, Mi; Yanlin, Wang; Xinyi, Li; Xuemin, Song (Frontiers in Pharmacology, 2022)
Kidney is the one of most vulnerable organ in sepsis, leading to sepsis-associated acute kidney injury(SA-AKI) which bring about not only the morbidity but also mortality of sepsis. Ferroptosis is a new kind death type of cells elicited by iron dependent lipid peroxidation, which participates in pathogenesis of sepsis. The aim of this study was to verify the occurence of ferroptosis in the SA-AKI pathogenesis and demonstrate that post-treatment with irisin could restrain ferroptosis and alleviate SA-AKI via activating Sirt1/Nrf2 signaling pathway. We established a SA-AKI model by cecal ligation and puncture (CLP) operation and an in vitro model in LPS-induced HK2 cells, respectively. Our result exhibited irisin inhibited the level of ferroptosis and ameliorate kidney injury in CLP mice, as evidenced by reducing ROS production, iron content, MDA level and increasing GSH level, as well as the alteration of ferroptosis-related protein (GPX4 and ACSL4) expression in renal, which was consistent with ferroptosis inhibitor ferrostatin-1 (Fer-1). Additionally, We consistently observed that irisin inhibited SA-AKI induced ROS accumulation, iron production, and ameliorated mitochondrial dysfunction in LPS-stimulated HK-2 cells. Furthermore, our result also revealed that irisin could activate Sirt1/Nrf2 signaling pathways both in vivo and vitro. However, the beneficial effect of irisin were weakened by EX527( an inhibitor of SIRT1) in vivo and by SIRT1 siRNA in vitro. In conclusion, irisin could protect against SA-AKI through anti-ferroptosis via the Sirt1/Nrf2 signaling pathway.